2018
DOI: 10.4103/ejd.ejd_322_17
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between tooth loss, body mass index, and hypertension in postmenopausal female

Abstract: Objective:This study aimed to investigate the relationship between tooth loss and the level of blood pressure with the hypothesis that tooth loss is associated with the increase of hypertension in postmenopausal women.Materials and Methods:Sixty postmenopausal female patients aged 51–68 years were included in the study to assess the relationship between tooth loss and the level of blood pressure. The information including sociodemographics, last menstruation period, hypertension history, and the duration of ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…of missing teeth Category: ≤ 3/4–14/ ≥ 15 Hypertension Category: hypertension/normotensive 1, 2, 3, 4 Individuals with ≥ 15 missing teeth have significantly higher risk of stage III hyper tension than those with ≤ 3 (aOR 1.03; 95% CI 1.03–1.64) Dar-Odeh et al 42 10,576 female patients from university clinic (dental) aged 18 years and older (Saudi Arabia) No. of missing teeth Category:No missing teeth/Having missing teeth Hypertension Category: hypertension/normotensive 1, 3, 4 In a linear regression model, missing teeth was marginally significantly associated with hypertension (p = 0.088) Al-Ahmad et al 43 60 postmenopausal women (Malaysia) No. of missing teeth Hypertension Category: hypertension/normotensive Postmenopausal women with hypertension showed more significant tooth loss compared to those with normal tension (p < 0.05) Delgado-Perez et al 44 60 patients in a health center (Mexico) No.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…of missing teeth Category: ≤ 3/4–14/ ≥ 15 Hypertension Category: hypertension/normotensive 1, 2, 3, 4 Individuals with ≥ 15 missing teeth have significantly higher risk of stage III hyper tension than those with ≤ 3 (aOR 1.03; 95% CI 1.03–1.64) Dar-Odeh et al 42 10,576 female patients from university clinic (dental) aged 18 years and older (Saudi Arabia) No. of missing teeth Category:No missing teeth/Having missing teeth Hypertension Category: hypertension/normotensive 1, 3, 4 In a linear regression model, missing teeth was marginally significantly associated with hypertension (p = 0.088) Al-Ahmad et al 43 60 postmenopausal women (Malaysia) No. of missing teeth Hypertension Category: hypertension/normotensive Postmenopausal women with hypertension showed more significant tooth loss compared to those with normal tension (p < 0.05) Delgado-Perez et al 44 60 patients in a health center (Mexico) No.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the number of teeth, 14 studies evaluated the number of missing teeth 38 , 39 , 41 45 , 47 , 50 , 51 , 55 , 57 , 58 , 59 while 10 studies evaluated the number of remaining teeth 40 , 46 , 48 , 49 , 52 54 , 56 , 61 , 60 . In the analyses, only four studies used measured values 43 45 , 47 while the other 20 categorized measured values. Categorizations were vastly different.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the results observed forces us to reflect and ask ourselves new questions and challenges, as whether periodontal disease is a marker or mediator or some patients may have a genetic or metabolic susceptibility 22 that might also play a part, as well as whether it affects only the SBP by some unknown mechanism or the periodontal treatment really has an initial effect on the BP but not maintained over time.…”
Section: Discussionmentioning
confidence: 96%
“…29 Yet, other studies (including only women) have found an association between severe tooth loss and arterial hypertension. 6,7,30 Therefore, the literature to date does not support a clear conclusion about gender-related differences in the association between severe tooth loss and arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…1-4 It is plausible that arterial hypertension is in the path of the association between tooth loss and atherosclerosis, since several studies have found significant associations between severe tooth loss and high blood pressure (BP), a condition that predisposes to the development of atherosclerosis. 5-8 Some of these studies were confined to specific groups (eg, postmenopausal women) or limited to small sample sizes, and may not be representative of the general population. Moreover, few studies have taken into account the effect of confounders on this association or the independent association between severe tooth loss and the different components of BP, that is, pulsatile [systolic BP (SBP) and pulse pressure (PP)], and steady [diastolic BP (DBP)] components.…”
Section: Introductionmentioning
confidence: 99%